2013
DOI: 10.1542/hpeds.2012-0091
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Language, Serious Adverse Events, and Length of Stay Among Hospitalized Children

Abstract: Hospitalized children from Spanish-speaking families had significantly longer hospital stays in association with an adverse event and may have increased odds of a serious or sentinel event. These findings suggest that an important component of patient safety may be to address communication barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Morse et al demonstrated that reduced inpatient LOS did not lead to more frequent admissions across 43 hospitals in the United States [9]. It is possible that patients admitted to Hospital A had greater medical complexity or illness severity, both of which have been associated with longer LOS [7, 8, 21]. We attempted to take this into account by adjusting for final diagnosis, but could not account for co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morse et al demonstrated that reduced inpatient LOS did not lead to more frequent admissions across 43 hospitals in the United States [9]. It is possible that patients admitted to Hospital A had greater medical complexity or illness severity, both of which have been associated with longer LOS [7, 8, 21]. We attempted to take this into account by adjusting for final diagnosis, but could not account for co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient LOS is used as a measure of quality of health service [6]. Adverse clinical events are associated with prolonged LOS, [7, 8] and there is evidence to suggest that shorter length of stay does not compromise care quality [9]. Few studies have examined factors associated with LOS for acute paediatrics and these have mostly looked at the association with socio-economic position (SEP) [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Poor communication between healthcare providers and patients could result in increased HAI rates, either directly or indirectly. 23 For example, ineffective communication could result in patients manipulating indwelling devices in a manner that could increase the risk of infection or result in prolonged hospital stays for unrelated reasons, which could also increase length of exposure to risk for HAIs. Limited English proficiency is known to be a risk factor for adverse events in hospitalized patients, 24 but we found no studies that specifically examine the role of language barriers in HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Language barriers in the health care setting are associated with increased cost, 2 decreased satisfaction 3,4 and adherence, 5,6 variation in testing and diagnosis, 2,7 and increased serious adverse events. [8][9][10][11] Both in-person and telephonic professional medical interpretation effectively mitigate the risks associated with language barriers, [12][13][14] but underutilization of professional interpreters is widespread. [15][16][17][18][19] Many providers choose to "get by" with nonproficient language skills, 20 Dr Lion conceptualized and designed the study, performed the analyses, and drafted the manuscript; Dr Ebel assisted with study design, participated in analysis planning and interpretation, and reviewed and critically revised the manuscript; Ms Rafton and Ms Hencz contributed to study design and reviewed and provided critical input on the manuscript; Dr Zhou provided critical input on study design and analysis, and reviewed and revised the manuscript; Dr Mangione-Smith participated in study design, contributed to analytic planning and interpretation of results, and critically revised the manuscript; and all authors approved the final manuscript as submitted.…”
mentioning
confidence: 99%